The Position of Choice of Forum and Alternative Dispute Resolution Principles in Contemporary Sharia-Based Property Dispute - Pratama, Abdul Hakim; Paserangi, Hasbir; Mufrih, Adi Nurhani; Talli, Abdul Halim; Mohd Al Adib bin Samuri (MILRev: Metro Islamic Law Review, 2025)
This study explores the legal position and implications of forum selection clauses and alternative dispute resolution (ADR) mechanisms in contemporary sharia-based property disputes. Although statutory regulations have governed the forum for Sharia economic dispute resolution—generally designating Religious Courts or Sharia Arbitration—practical implementation still raises interpretative challenges, particularly in cases involving third parties or property rights. Using a qualitative method with statutory, comparative, and case study approaches, the research reveals that forum choice clauses in sharia contracts are legally valid and binding, as supported by Supreme Court Circular Letter (SEMA) No. 4 of 2016. However, in practice, disputes involving secondary agreements or third-party claims over property often shift jurisdiction from the Religious Court to the District Court. This occurs especially when the primary issue concerns ownership or property rights tied to sharia-based transactions, such as murabahah, ijarah, or rahn contracts. The findings underscore a dissonance between normative legal frameworks and judicial practice, leading to overlapping authorities and legal uncertainty. The study also identifies a tendency among judges to prioritize the object of dispute (e.g., property or collateral) over the contractual nature, thereby affecting the determination of appropriate forum jurisdiction. This research contributes academically by offering a clearer understanding of how forum selection clauses operate within Indonesia's dual court system and by advocating for a more integrated legal interpretation that aligns Islamic legal principles with national procedural law. Ultimately, it highlights the urgency of harmonizing jurisdictional boundaries to strengthen the enforcement and credibility of sharia economic law in resolving property-related disputes.